KOLABORASI PENGUATAN RENCANA IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH - Asep, Asep; Andison, Andison (Universitas Pattimura, 2023)
Improving the quality of education is one of the potentials that the government continues to develop in improving the quality of human resources. The development of an independent curriculum is a new breakthrough by the Ministry of Education and Culture in responding to challenges in the world of education in the current era. Community service carried out by the academic community is an effort to collaborate in the implementation of an independent curriculum. community service in this case is carried out in collaboration with SMK Negeri 1 Koto Besar in developing a program planning for implementing an independent curriculum. the method used in implementing collaboration is through strengthening and recommending implementation programs. Through community service activities, the results obtained are that teachers need special assistance in understanding each platform of the independent curriculum, recommendations in the form of a literacy corner named the term